Ответ:
1). -(m - 38) + (412 + m)
=450
2). -(243 + X-b) - (243 + b-x)
=-486
3). -(153-x+ a) - (x-a- 253)
=100
4). -(a-x) - (51 + х) +a-51
=-202
5). (b-x) - (a-x) + (a-b)
=0
6). -(a + 33) - (x-a) - 33 +х
=-66
7). (243 + 11) - (b+ 243) + (0-11)
=-b
8). (153-x+a) - (х - 153 - a) - а
=-2x+a
9). - (а - 121) - (1-a) - (21 - а)=99+a
Пошаговое объяснение:
4 к 6 - 4/6
12 к 18 = 12/18
4/6 = 12/18
12 × 6 = 4 × 18
72 = 72
0 = 0
Но чтобы от 4 к 6 получить 12 к 18, нужно и числитель, и знаменатель умножить на 3.
Ответ:3*1 2/3-2= 3*5/3-2=5-3=2
Пошаговое объяснение: